Nereiphylla pusilla (Polychaeta, Phyllodocidae) rediscovered and redescribed from Sicily - Pleijel, Fredrik; Mackie, Andrew S.Y. (Vie et Milieu, 1993)
Nereiphylla pusilla (Claparède, 1870) is redescribed and a neotype designated from newly collected specimens from eastern Sicily. It is distinguished from other European members of the genus by the combination of small size at maturity (3-5 mm long), possession of large eggs (about 150 µm in diameter) and short swollen dorsal, ventral and pygidial cirri. The species is currently known only from the north-western Mediterranean, Phyllodoce nana Saint-Joseph, 1906 from Cannes being a junior synonym. Comparisons with other species of Nereiphylla are provided and N. mimica Eibye-Jacobsen, 1992 from Belize is considered the closest related species.
World Polychaeta Database (WPolyDb)